2015
DOI: 10.1016/j.cell.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Healthy Growth and Nutrition through the Gut Microbiota

Abstract: Microbiota assembly is perturbed in children with undernutrition, resulting in persistent microbiota immaturity that is not rescued by current nutritional interventions. Evidence is accumulating that this immaturity is causally related to the pathogenesis of undernutrition and its lingering sequelae. Preclinical models in which human gut communities are replicated in gnotobiotic mice have provided an opportunity to identify and predict the effects of different dietary ingredients on microbiota structure, expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(105 citation statements)
references
References 81 publications
(98 reference statements)
6
93
0
Order By: Relevance
“…Machine-learning methods (Random Forests) have yielded sparse models composed of a limited number of highly indicative age-discriminatory bacterial strains that together form a signature for defining the normal developmental biology of this microbial organ (3,5). The fact that timedependent changes in the representation of these indicative bacterial strains was similar across biologically unrelated individuals living in distinct geographic areas [e.g., Malawi and Bangladesh (3)] suggests that a set of (still-to-be-defined) rules govern development/differentiation of this organ which is composed of multiple cell lineages (taxa).…”
Section: Discussionmentioning
confidence: 99%
“…Machine-learning methods (Random Forests) have yielded sparse models composed of a limited number of highly indicative age-discriminatory bacterial strains that together form a signature for defining the normal developmental biology of this microbial organ (3,5). The fact that timedependent changes in the representation of these indicative bacterial strains was similar across biologically unrelated individuals living in distinct geographic areas [e.g., Malawi and Bangladesh (3)] suggests that a set of (still-to-be-defined) rules govern development/differentiation of this organ which is composed of multiple cell lineages (taxa).…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, microbial shifts in the intestinal community are coincident with the diet 110 ; furthermore, remodeling of the intestinal microbial community during the introduction of solid food appears to be dependent on whether infants were breastfed. 86 The quality and type of foods within a given diet influence the composition of the microbiota and, ultimately, host health (reviewed by Mitsuoka 111 and Subramanian et al 112 .). A recent study found that malnutrition is associated with intestinal microbiota immaturity, which was only partially ameliorated by nutritional intervention in Bangladeshi children.…”
Section: Environmental Enteropathy and Genetic Predispositionmentioning
confidence: 99%
“…The development of the microbiome is influenced by mode of infant delivery, dietary intake, genetic profile, and environmental exposures [40-42]. Malnourished children appear to demonstrate abnormal microbiome development, characterized by less microbial diversity, distinguished by fewer bacterial taxa and lower relative abundance as compared to normally nourished children of the same age [43, 44].…”
Section: The Gut Microbiota and Childhood Growthmentioning
confidence: 99%